Beyond Employability: Defamiliarizing Work-Integrated Learning with Community-Engaged Learning - Brabazon, Honor; Esmail, Jennifer; Locklin, Reid; Stirling, Ashley (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2019)
Within the context of an increasing interest in forms of work-integrated learning (WIL) among governments and institutions of higher education, this essay explores the relation between WIL and community-engaged learning (CEL) in order to argue that the structural and self-critique apparent in much CEL scholarship can serve as a model to WIL scholars and practitioners. CEL has undergone a rigorous process of self-examination in recent years, a process that has encouraged its advocates to think carefully about their core assumptions, appropriate learning objectives, and best practices in the field. In this way, we argue, whether or not CEL is classified as a form of WIL, it can serve to defamiliarize many of WIL’s assumptions and to invite self-reflection in the field as a whole. In the first half of the essay, we provide background for the conversation, first in the Canadian context, and then in the broader scholarship of CEL. In the second half, we offer three case studies that illustrate both the distinctive characteristics of CEL and, in the last case, how these characteristics might strengthen the practice of traditional WIL.